Supporting early mathematical development : practical approaches to play-based learning - McGrath, Caroline (London : Routledge, 2010)
This highly topical resource offers a blend of theory and practice that will enable you to deliver successful mathematical education from birth to eight year olds. The book links current practice and fundamental early years principles and makes suggestions for creating effective pedagogies in maths teaching.
Includes bibliographical references and index
Keywords: Mathematics -- Study and teaching (Early childhood); Early childhood education